PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS PERMAINAN TRADISIONAL UNTUK KELAS III SEKOLAH DASAR: Traditional Games, Mathematics Learning, Learning Media - Yobel, Gregorio Arkho (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to develop a traditional games guidebook for third-grade elementary school mathematics learning that is engaging and effective. The research method used Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The product was developed based on needs analysis at Bhaktikarya Elementary School, which showed that mathematics learning was still monotonous and students quickly became bored. The developed guidebook integrates four traditional games (marbles, tic-tac-toe, hopscotch, and lurah-lurahan) modified to suit mathematics materials in theme 1 sub-theme 4 and theme 3 sub-theme 3. Validation results by mathematics experts, traditional games experts, and classroom teachers showed an average score of 3.46 (categorized as